Bureaucracy - Chaves Giraldo, Pedro (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
This article deals with the debate on bureaucracy in the context of the changes occurred within our societies in the last decades. According to the author, these changes compel to rethink Weber’s doctrine of bureaucracy.